Monitoring water quality : pollution assessment, analysis, and remediation - Ahuja, Satinder, 1933- (Amsterdam : Elsevier, 2013)
Water is the second most important essential material for human survival. Even though Earth is compsed largely of water, fresh water comprises only 3% of the total water available to us. Of that, only 0.06% is easily accessible. To ensure sustainability of water that is safe for drinking, fish, wildlife, industry, irrigation, and recreation, it is critical to explore water quality in greater detail. Over the last 10 years, improved laboratory techniques have led to the discovery of microbial and viral contaminants, pharmaceuticals, and endocrine disruptors in our water that were not monited previously. This book covers at length the following topics: water quality issue (natural and human-related), monitoring contaminants (including pharmaceutcal and endocrine disruptors) and remediation of water contamination. deals with water, the second most essential ingredient to sustain our life. The author discusses methods for monitoring a variety of water contaminants and describes various problemens and solutions for sustainability of water quality worldwide. Up-to-date information on new chemicals and their enviromental impacts is paramount in such a changing environment. The book covers the continual influx of new pollutants into the environment, as well as new pollutant impacts continually being found from existing chemicals in use and provides up-to-date information on prevalence, analysis, and treatment critically needed by scientists and regulators--
Includes bibliographical references and index.
Keywords: Water quality -- Measurement